IMPLEMENTASI BATIK SUROSOWAN DENGAN GAYA MODERN KONTEMPORER PADA LOBBY KANTOR BPKP BANTEN - Aulia, Muhamad Fikri; Kusnaedi, Iyus (Department of Interior Design, Faculty of Engineering, Lancang Kuning University, Indonesia, 2024)
The lobby is a crucial element in every office building, playing a significant role as the primary area for guest reception that first imparts an impression. Therefore, it's vital for the office lobby to reflect an ambiance that mirrors the identity and values of the institution. This study aims to explore the application of the Surosowan batik motif in the aesthetic elements of the lobby's interior to establish a strong identity for Banten culture. The main focus of the research is to enhance the office's identity through innovative use of materials, especially metals, implemented in the batik motif on the lobby's wall spaces. This is intended to create a balance of local cultural values in line with the vision and mission of the BPKP Banten Office. The research method employed is qualitative, focusing on the search and understanding of data relevant to the theories of Banten Culture, Surosowan Batik, and the Vision and Mission of the BPKP Banten Office as a solid foundation in designing creative solutions. The result of this study is the implementation of the Surosowan Batik motif in wall treatments using metal materials. The findings of this research can provide practical and creative guidelines in applying the Surosowan batik motif to the interior design of office lobbies, ultimately enriching the office space with a distinctive cultural identity.